Anti-acidogenic and anti-biofilm activity of 5, 6, 8-trihydroxy-7-methoxy-2-(4-methoxyphenyl)-4H-chromen-4-one. (October 2018) - Ngabaza, Thamsanqa; Moeno, Sharon; Patel, Mrudula
Abstract: Objectives: Crude extracts of Dodonaea viscosa var. angustifolia (DVA), has shown to have anticariogenic property. However the compound responsible for this activity has not been identified. The aim of this study was to investigateanti-acidogenic and anti-biofilm activity of a flavone 5, 6, 8-Trihydroxy-7-methoxy-2-(4-methoxyphenyl)-4 H -chromen-4-one isolated from D. viscosa var. angustifolia (DVA) in cariogenic bacteria Streptococcus mutans. Methods: The crude extract from DVA leaves was fractionated into six fractions (F1-F6) using chromatography. The Minimum Inhibitory Concentrations (MIC) and Minimum Bactericidal Concentration (MBC) were determined. The effect of the six fractions on biofilm formation and acid production were investigated. The most active fraction (F5) was further fractionated, purified, identified and elucidated using GC-MS and NMR. The anticariogenic property of this purified compound was established. Results were analyzed using Wilcoxon rank-sum test (Mann-Whitney). Results: The MIC and MBC of the fractions (F1-F6) and crude extract ranged from 0.39 to 12.5 mg/ml. F5 showed the lowest MBC. At 0.2 mg/ml, F5 reduced biofilm formation by 93.3% and reduced acid production in S. mutans . Subfraction F5.1 showed higher antimicrobial activity compared to the crude extract and F5. Purified F5.1 was identified as 5, 6, 8-Trihydroxy-7-methoxy-2-(4-methoxyphenyl)-4 H -chromen-4-one (TMMC). TMMC inhibited biofilm formation at both 6 h (94% reduction) and 24 h (99% reduction), which was higher compared to the crude extract (87% reduction at 0.78 mg/ml after 6 h). TMMC also exhibited a higher inhibitory effect on acid production compared to the crude extract. Conclusion: Flavone 5, 6, 8-Trihydroxy-7-methoxy-2-(4-methoxyphenyl)-4 H -chromen-4-one derived from DVA has anti- S. mutans, anti-biofilm and anti-acidogenic activity therefore it has a potential for use in the oral cavity to prevent dental caries. Graphical abstract: Highlights: Flavone 5, 6, 8-trihydroxy-7, 4 l -dimethoxyflavone derived from DVA has anti- S. mutans activity. Fifty μg/ml of flavone caused 94% reduction in the biofilm formation. Flavone significantly reduced acid production by S. mutans. It has a potential to be developed as an anticariogenic therapeutic product.